Interplay between maternal and neonatal vitamin D deficiency and vitamin-D-related gene polymorphism with neonatal Birth anthropometry - Lee, Siew Siew; Ling, King Hwa; Tusimin, Maiza; Subramaniam, Raman; Rahim, Kartini Farah; Loh, Su Peng (Multidisciplinary Digital Publishing Institute, 2022)
Vitamin D deficiency during pregnancy has been associated with poor foetal growth and neonatal birth anthropometry. However, the associations were inconsistent and could be confounded by neonatal vitamin D status and genetic factors. Until recently, limited studies have concomitantly examined the effect of maternal and neonatal vitamin D deficiency and vitamin D-related single nucleotide polymorphisms (SNPs) on neonatal birth anthropometry. This study aims to examine the independent and combined effects of maternal and neonatal vitamin D deficiency and vitamin-D-related SNPs on neonatal birth anthropometry. This cross-sectional study included 217 mother–neonate dyads recruited from Hospital Serdang, Selangor, Malaysia, between 2015 and 2017. Plasma 25-hydroxyvitamin D (25OHD) concentration was measured in maternal and umbilical cord blood using ultra-high-performance liquid chromatography (UHPLC). Maternal and neonatal vitamin D Receptor (VDR) SNP (rs2228570) genotypes were determined using high-resolution melting (HRM). Group-specific component (GC) SNPs (rs4588 and rs7041) genotypes were determined using restriction fragment length polymorphism. Our results showed that: (1) maternal vitamin D deficiency (25OHD < 30 nmol/L) was inversely associated with birth weight, head circumference and crown–heel length; (2) neonatal SNPs, VDR rs2228570 and GC rs4588, were significantly associated with birth weight and head circumference, respectively; and (3) a potential interaction was observed between maternal VDR rs2228570 with maternal vitamin D deficiency on head circumference. These findings suggest that the underlying mechanisms of vitamin D on foetal growth are likely to be localised in the maternal compartment, mediated through the placenta, rather than through cellular mechanisms within the foetus. Further large-scale studies are warranted to validate and extend these findings.